TINJUAN YURIDIS MENGENAI PERKAWINAN CAMPURAN DAN AKIBAT HUKUMNYA BERDASARKAN UU NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Dicky Charly Makuku (Sekolah Tinggi Pariwisata Mataram, 2022)
Marriage is one of the significant occasions in human existence, in human existence with its different legitimate outcomes. Hence the law directs this issue of marriage exhaustively. Indonesia has appropriately directed marriage techniques in Regulation No. 1 of 1974. This Marriage Regulation expects to control the relationship of an ideal, blissful and everlasting life in a family to make fondness and shared love in the family. In Regulation No. 1 of 1974 on Marriage (hereinafter alluded to as the Marriage Regulation), the importance of Marriage will be,